Fiqih Rational about Zakat and In Grants Compilation of Sharia Economic Law (KHES) - Nurhadi Nurhadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2019)
This study aims to determine the rational fiqh about zakat and grants in the Compilation of Sharia Economic Law (KHES). This research method uses a qualitative concept, with a normative juridical approach in concreto and legal synchronization, while the Risert library research type (literature) and data analysis techniques use the contents analysis method with the benefit of measuring instruments. The result is that zakat and grants have an important role in life berketuhanan, community and state, in the science of fiqh propulsion has maqashid hifzu al-Maal (memlihara treasure) for the sanctity of property, the soul also keep the despicable nature for the benefit of the afterlife, so that the sacred property of property other people. Zakat and grants are compulsory logging and circumcision, both of which are dimensions of good deeds, namely the dimensions of worship, social and economic. Awareness of the ummah in performing zakat, as well as the idolatry that is given to the authorized institution to manage and distribute it, while implementing regulations as a provision in accordance with KHES Article 684 that the State has the right to withdraw zakat and penalties for people who are reluctant to pay zakat, this can improve economic welfare the ummah and significantly reduce poverty.